2006
DOI: 10.1186/1746-4269-2-41
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal plants used by the people of Manang district, central Nepal

Abstract: Background: The district of Manang (2000 -6000 m) is located in the Central Himalayas, Nepal. The majority of local inhabitants of the area are Gurungs, of Tibetan origin. The remoteness of the region has resulted in continued use of plants as medicine in an area where the ethnobotany has sparsely been documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(102 citation statements)
references
References 4 publications
4
90
0
1
Order By: Relevance
“…The diversity of plant parts found by this study agrees with the results obtained from other ethnomedicinal studies; Lulekal et al (2008), Mesfin et al (2009, and Awas and Demissew (2009) all reported that leaves were the plant parts most used in medicine preparations. The preference of leaves to other plant parts could be due to (1) ease of collection and preparation, (2) preparation of medicinal teas (Gazzaneo et al 2005), and/or (3) the presence of more bioactive ingredients in leaves developed in response to phytophagous organisms since leaves are the most vulnerable parts of a plant (Bhattarai et al 2006). Lulekal et al (2008) and Yineger et al (2008) also found that most prepared remedies were used immediately after harvest.…”
Section: Ailments Treated Plant Parts Used and Modes Of Remedy Prepmentioning
confidence: 99%
“…The diversity of plant parts found by this study agrees with the results obtained from other ethnomedicinal studies; Lulekal et al (2008), Mesfin et al (2009, and Awas and Demissew (2009) all reported that leaves were the plant parts most used in medicine preparations. The preference of leaves to other plant parts could be due to (1) ease of collection and preparation, (2) preparation of medicinal teas (Gazzaneo et al 2005), and/or (3) the presence of more bioactive ingredients in leaves developed in response to phytophagous organisms since leaves are the most vulnerable parts of a plant (Bhattarai et al 2006). Lulekal et al (2008) and Yineger et al (2008) also found that most prepared remedies were used immediately after harvest.…”
Section: Ailments Treated Plant Parts Used and Modes Of Remedy Prepmentioning
confidence: 99%
“…The lack of modern and government facilities and remote geographical features of tribal area, as well as a strong belief in folk knowledge continue the preference for traditional knowledge for their life style (Shandesh Bhattarai et al, 2006). …”
Section: Recommendationsmentioning
confidence: 99%
“…Aconitum naviculare and Neopicrorhiza scrophulariiflora are among the most prioritized medicinal plants in Manang in terms of ethnomedicinal uses (Bhattarai et al 2007). A. naviculare shows narrow distribution range in the Himalayas, and it has been reported only from trans-Himalayan regions, such as Tibet (Gao et al 2004) and some parts of Nepal including Dolpo (Lama et al 2001), Mustang (Bista and Bista 2005, Chetri et al 2006, Ohba et al 2008 and Manang (Bhattarai et al 2007, Shrestha et al 2007a.…”
Section: Introductionmentioning
confidence: 99%